“What They Do That We Don’t Do”: Ethnic Identity Representation In Students’ Intercultural Experiences - Dalib, Syarizan (2015)
The rapid process of emigration and immigration in this 21 st century has resulted in a remarkable population change across national borders. This trend has led to the re-assertion of ethnic identities and the attention on ethnic differences as an important agenda for many societies. Accordingly, ethnic identities have become relevant in how we understand the process of communication between diverse people in this global world. Despite the consciousness of ethnic identities, the tendency to approach intercultural communication through the lens of nationality remains dominant in the field. As researchers are influenced by the idea that “national culture” is shared by all cultural members, utilizing nationality as the unit of analysis often forces researchers to analyse the unifying elements that describe the whole populations and ignore differences between groups. Consequently, such tendency has led researchers to utilize homogenizing views in their analysis, hence simplifying the complex nature of heterogeneous environment where people of different ethnic identities may co-exist. As such, scholars have pointed out that ethnic identities are not fully addressed in the analysis of intercultural communication. This study explores the representation of ethnic identities in intercultural experiences among diverse students in a Malaysian university. In-depth phenomenological interviews were conducted with fifteen participants. Two themes emerged from the data analysis that elucidates the intricate nature of ethnic identities in students’ intercultural experiences: (i) identifying self as an ethnic being and (ii) encountering differences between self and the other. The central metaphorical interpretation that emerged from this study, that is, “what they do that we don’t do”, recognizes not only participants’ consciousness of their ethnic identities that filter their interpretations of selves and the other in their communication, but also consciousness of dissimilar communication behaviours. The findings of this study offer an interesting insight on ethnic identities as it is situated within students’ intercultural experiences. It contributes into thinking through the complex representation of ethnic identities as a framework for understanding the process of intercultural communication.